Arming shoes of the fifteenth century - Volken Marquita (Acta Periodica Duellatorum)
Military footwear for the fifteenth century includes arming shoes worn under sabatons. Written sources suggest arming shoes and footwear used for fighting were ordinary shoes adapted for the purpose. Archaeological footwear was examined for signs of such modifications. Medieval shoe technology is presented, showing the range of footwear and its uses and gait biomechanics. Based on experiences from re-enactors wearing armours, medieval shoe styles are discussed for appropriateness as arming shoes. The question of why medieval military footwear shows no purposed development is addressed.